2023
DOI: 10.3389/fenvs.2022.1114940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil grain size and solution chemistry on the transport of biochar nanoparticles

Abstract: Biochar nanoparticles (BC-NP) have attracted significant attention because of their unique environmental behavior, some of which could potentially limit large-scale field application of biochar. Accurate prediction of the fate and transportability of BC-NP in soil matrix is the key to evaluating their environmental influence. This study investigated the effects of soil grain size and environmentally relevant solution chemistry, such as ionic strength (cation concentration, 0.1 mM–50 mM; cation type, Na+, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…Since the diffusion coefficient of nanoparticles is small, they are not easy to diffuse into small pores with low concentrations and slow flow rates. Therefore, consistent with previous studies, the results of this study show that the ability of nanoparticles to migrate downward is relatively weak in fine-textured soils (silt loam), while the migration ability of NBC gradually increases in loam and sandy loam [ 26 , 50 , 51 ]. In addition, soil properties such as pH, CEC , and negative Zeta potential can alter the interaction energy and adsorption capacity between particle systems.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since the diffusion coefficient of nanoparticles is small, they are not easy to diffuse into small pores with low concentrations and slow flow rates. Therefore, consistent with previous studies, the results of this study show that the ability of nanoparticles to migrate downward is relatively weak in fine-textured soils (silt loam), while the migration ability of NBC gradually increases in loam and sandy loam [ 26 , 50 , 51 ]. In addition, soil properties such as pH, CEC , and negative Zeta potential can alter the interaction energy and adsorption capacity between particle systems.…”
Section: Discussionsupporting
confidence: 92%
“…Chen et al found that by suddenly reducing the ionic strength of the carrier solution by five times (from 50 mM to 10 mM), a large number of BC colloidal particles retained on the surface of soil particles were released [ 25 ]. Additionally, the type of ions also affects the migration properties of NBC: divalent cations (Ca 2+ ) exhibit greater efficacy in inhibiting the migration of NBC in soil than monovalent cations (Na + ) [ 26 ]. This is mainly due to the fact that higher-valent cations are more likely to form bridges with NBC, leading to NBC aggregation.…”
Section: Introductionmentioning
confidence: 99%